Is monetary policy in the Eurozone less effective than in the US? - Paul De Grauwe; Cláudia Costa Storti (Center for Economic Studies and ifo Institute (CESifo), 2005)
There is a wide consensus that the existence of structural rigidities in the Eurozone reduces the effectiveness of the ECB's monetary policies. In order to test this ?ECB-handicap? hypothesis, we perform a meta-analysis of the effects of monetary policies in the US and the Eurozone countries. This consists in collecting the estimated transmission coefficients obtained from published econometric studies. Meta-analysis then allows us to control for a number of factors that can affect these estimated coefficients. We conclude that there is no evidence for the hypothesis that the ECB is handicapped in using monetary policies for the purpose of stabilizing output compared to the US.
Keywords: E58; E50; E52; 330; Geldpolitik; Konjunkturpolitik; Wirtschaftspolitische Wirkungsanalyse; Transmissionsmechanismus; Vergleich; EU-Staaten; USA